Estructura y dinámicas de las Mesas de Educación Física de Medellín en relación con los procesos de formación permanente de maestros (2013)
ABSTRACT: This text is the result of a research called "The participation of the Mesas de Educación Física de Medellin in the ongoing training of teachers from the perspective of human development", developed in the framework of the Master in motor functions and human Development at the University of Antioquia. The article reports on the dimensions: members, assistance and temporality shaping the structure and dynamics of the teaching collectives of physical education and their relation in the process of ongoing training. This is a qualitative study which uses the hermeneutic-dialectic method. The information was collected through interviews with teachers of the teaching collectives, group discussions with the coordinators of the teaching collectives and the content analysis of the minutes of the meetings. We conclude that ongoing training processes are determined, also of their strategies and methodology configurative, by the structure and dynamics of the training device.